Innovation Amid Pandemic: Construction of a COVID-19 Intensive Care Unit Surge Care Delivery Model. Issue 1 (January 2022) - Geyer, Latrina T.; Bennett, Stephanie G.; Atkins, W. Jason; Baird, Marianne; Bannan, Ryan; Cunningham, Tim; Davis, Mardi J.; Zellinger, Mary
Abstract : This article details a shared leadership structure and decision-making processes used to construct an innovative and evidence-based care delivery model for safety and optimal outcomes in the intensive care unit during the novel coronavirus (COVID-19) pandemic. Insights into ways professional development practitioners can facilitate changes in care delivery models, support nurses in their professional roles, and contribute to improved patient care outcomes during the COVID-19 pandemic are provided.